Shakespeare and the uses of comedy - Bryant, J. A. (Joseph Allen), 1919-1999 (University Press of Kentucky, 1986)
In Shakespeare's hand the comic mode became an instrument for exploring the broad territory of the human situation, including much that had normally been reserved for tragedy. Once the reader recognizes that justification for such an assumption is presented repeatedly in the earlier comedies -- from The Comedy of Errors to Twelfth Night -- he has less difficulty in dispensing with the currently fashionable classifications of the later comedies as problem plays and romances or tragicomedies and thus in seeing them all as manifestations of a single impulse. Bryant shows how Shakespeare, early a.